Synthesis and Antimicrobial Activity of N-(6-Carboxyl Cyclohex-3-ene Carbonyl) Chitosan with Different Degrees of Substitution. (23rd October 2016) - Badawy, Mohamed E. I.; Rabea, Entsar I.
Abstract : Five products ofN -(6-carboxyl cyclohex-3-ene carbonyl) chitosan as antimicrobial agents were prepared by reaction of chitosan with tetrahydrophthalic anhydride (THPA) at different degrees of substitution (DS). The antimicrobial activity was evaluated against four plant bacteria and eight fungi. The results proved that the inhibitory property and water solubility of the synthesized chitosan derivatives, with increase of the DS, exhibited a remarkable improvement over chitosan. The product with a DS of 0.40 was the most active one with MIC of 510, 735, 240, and 385 mg/L against Erwinia carotovora, Ralstonia solanacearum, Rhodococcus fascians, and Rhizobium radiobacter, respectively, and also in mycelial growth inhibition against Alternaria alternata (EC50 = 683 mg/L), Botrytis cinerea (EC50 = 774 mg/L), Botryodiplodia theobromae (EC50 = 501 mg/L), Fusarium oxysporum (EC50 = 500 mg/L), F. solani (EC50 = 260 mg/L), Penicillium digitatum (EC50 = 417 mg/L), Phytophthora infestans (EC50 = 298 mg/L), and Sclerotinia sclerotiorum (EC50 = 763 mg/L). These compounds based on a biodegradable and biocompatible chitosan could be used as potentially antimicrobial agents in crop protection instead of hazardous synthetic pesticides.